THE YAKUT BRANCH OF Y-CHROMOSOME AS A PART OF THE HAPLOGROUP N-M2016 - Dmitry S. Adamov (Siberian Research, 2022)
Based on the massive parallel sequencing, phylogenetic tree of the Y-chromosomal haplogroup N-M2016 was built. The branch N-M1982 of Yakut-Sakha men majority is located on the tree. The ages of tree branching nodes are estimated. Time to the most recent common ancestor (TMRCA) 970 ± 210 years BP (“present” defined as AD 1950) of one of the main Yakut male lineages N-M1991 is confirmed by accelerator mass spectrometry dating of a sample of the ancient man Yana Young [1] who died about 766 yBP. A sharp increase in the number of Yakut-Sakha ancestors observed on the Yakut branch N-M1982, began from 1320 ± 100 AD. Age of the population explosion is consistent with the radiocarbon dating of the Kulun-Atakh archaeological culture sites.